Angka Harapan Hidup, Tingkat Pengangguran Terbuka, Harapan Lama Sekolah Terhadap IPM Jawa Timur 2010-2024 - Cintya Putri Maharani; Hendry Cahyono (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This paper reviews the implications of Life Expectancy (LE), Open Unemployment Rate (OUR), and Expected Years of Schooling (EYS) on the Human Development Index (HDI) in East Java from 2010 to 2024. It uses time series data from the Central Statistics Agency and multiple linear regression analysis with Stata. Prior to analysis, tests for autocorrelation, normality, multicollinearity, and heteroscedasticity were executed to verify the integrity of the process. This outcomes show that all three variables simultaneously have a significant impact on the Human Development Index (HDI). Partially, Life Expectancy (LE) and Expected Years of Schooling (EYS) have a positive significant effect, with Expected Years of Schooling (EYS) as the dominant factor. Interestingly, the Open Unemployment Rate (OUR) also showed a positive relationship with the Human Development Index (HDI), indicating the existence of structural factors such as increased labor force participation, transition from the informal to the formal sector, or other variables that require further study. This model has high explanatory power with an Adjusted R-squared of 0.9657, showing that 96.57% of the variation in the Human Development Index (HDI) can be explained by these variables.